قصة اللغة العربيّة بالمغرب الأوسط (الجزائر).: The Story Of The Arabic Language In The Middle Maghreb (algeria) . - لعشبي, عقيلة (Maalim, 2021)
This research paper presents, in a brief word, the linguistic and cultural reality of the Central Maghreb (Algeria) before and after the Arab-Islamic conquest, because the Middle Maghreb was the focus of attention of those who aspired to it since the distant centuries BC and its rule of great empires and states, but the languages and cultures of all the colonialists who succeeded His judgment of the Greeks, Romans and Romans did not affect him and did not care about it as much as he loved the language of the Arab conqueror and immersed himself in his culture and religion, so he imprinted himself with the character of Arabism and Islam for eternity.